2020
DOI: 10.3390/microorganisms8111754
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance and Microbial Community Structure of Two Outdoor Pilot-Scale Photobioreactors Treating Digestate

Abstract: This study aimed at examining and comparing the nutrient removal efficiency, biomass productivity and microbial community structure of two outdoor pilot-scale photobioreactors, namely a bubble column and a raceway pond, treating the liquid fraction of an agricultural digestate. Bacterial and eukaryotic communities were characterized using a metabarcoding approach and quantitative PCR. The abundance, composition, diversity, and dynamics of the main microbes were then correlated to the environmental conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Thus, the results described above seem to suggest that Tetradesmus survived in organic wastes that were not characterized for extreme chemical-biological parameters, unlike Chlorella, which seemed to be much less affected by chemical-biological parameters of the organic wastes. On the other hand, the presence of Tetradesmus excluded (or strongly reduced) the presence of Chlorella, suggesting that in the absence of extreme growing conditions the former, when present, grew better than the latter (Bani et al, 2020). This fact suggested that extreme chemical-biological parameters selected Chlorella.…”
Section: Chemical-biological Features Of Wastes Vs Acs Isolation and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the results described above seem to suggest that Tetradesmus survived in organic wastes that were not characterized for extreme chemical-biological parameters, unlike Chlorella, which seemed to be much less affected by chemical-biological parameters of the organic wastes. On the other hand, the presence of Tetradesmus excluded (or strongly reduced) the presence of Chlorella, suggesting that in the absence of extreme growing conditions the former, when present, grew better than the latter (Bani et al, 2020). This fact suggested that extreme chemical-biological parameters selected Chlorella.…”
Section: Chemical-biological Features Of Wastes Vs Acs Isolation and ...mentioning
confidence: 99%
“…The driving forces structuring microbial communities are concurrently regulated by both external factors such as chemical-biological parameters of the growth media and internal factors such as the interaction between eukaryotes and prokaryotes (Bani et al, 2020).…”
Section: Chemical-biological Features Of Wastes Vs Acs Isolation and ...mentioning
confidence: 99%
“…The alternative could come in the form of algae by-products sourced from biotechnological industries. Industries of importance include fuel production [8] and when algae are used as biofilters to remove nutrients or contaminants [9,10] or to ameliorate carbon emission from various factories [11]. The concept of biofilters is of particular interest in extensive grazing systems of northern Australia since it has the potential to be linked to the development of silvopastoral plans for rehabilitating mine sites with the algae produced in wastewater being used as feed for livestock or organic fertilizer during the implantation of trees or to increase pastures productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor open systems (i.e., raceway ponds, bubble columns, flat panels) are considered so far as the most viable method of microalgal cultivation on wastewaters [ 13 ], even if complex and dynamic microbial consortia are formed inside [ 14 , 15 ]. A contribution to this field derives from a study, included in this Special Issue, which examined and compared the nutrient removal efficiency, biomass productivity, and microbial community structure of two outdoor pilot-scale photobioreactors (bubble column and raceway pond) [ 13 ].…”
mentioning
confidence: 99%
“…Outdoor open systems (i.e., raceway ponds, bubble columns, flat panels) are considered so far as the most viable method of microalgal cultivation on wastewaters [ 13 ], even if complex and dynamic microbial consortia are formed inside [ 14 , 15 ]. A contribution to this field derives from a study, included in this Special Issue, which examined and compared the nutrient removal efficiency, biomass productivity, and microbial community structure of two outdoor pilot-scale photobioreactors (bubble column and raceway pond) [ 13 ]. Data obtained, including the characterization of bacterial and eukaryotic communities using a metabarcoding approach and quantitative PCR, highlighted a different behavior and a different composition of the microbial communities, which were subjected to variations of the environmental conditions as well as of the reactors’ operational parameters.…”
mentioning
confidence: 99%